Fair - Hussain, Hamza; Kowlessur, Yuktha (First Peoples Child & Family Review, 2018)
The grade 3/4 and grade 7 class at Ross Drive Public School worked together to learn about treaties, Shannen Koostachin, and Shannen’s Dream. The students were asked to think about what a safe and comfy education might look like and why it is unfair that Shannen Koostachin had to fight for this right. This poem reflects what two students, Hamza and Yuktha, learnt.